The factor analysis of organizational commitment, job satisfaction and performance among lecturers in Batam - Hazriyanto, Hazriyanto; Ibrahim, Badaruddin (Penerbit UTHM, 2019)
This article intended to determine the important elements in commitment, satisfaction and job performance of university lecturers. This study involved 179 respondents from 3 universities located in Batam, Indonesia. The survey instrument had used a 5-point Likert scale to obtain feedback. Overall, the survey had achieved a very high level of reliability for organizational commitment, job satisfaction, and job performance. The data obtained was processed using exploratory factor analysis (EFA) to examine the structure of commitment, satisfaction, and performance factors. Overall, the instrument, which was the questionnaire, was valid. It was found, based on the EFA, that the three important factors were commitment, satisfaction, and performance. Hence, how could the findings significantly solve the problem statement as well as state the vision and potential of future studies. The Rotated Component Matrix showed the correlation between items and the factors after the Varimax rotation. Factor 1 contained 13 items, Factor 2 contained 12 items, while Factor 3 contained 11 items. It was found that items in Factor 1 could be under the “Commitment Factor”, items in Factor 2 could be under the “Performance Factor”, while items under factor 3 could be under the “Satisfaction Factor”. The outcome of this study could act as a guideline for lecturers to excel in their careers as well as assist institutions to develop effective evaluations.